Fisetin Protects HaCaT Human Keratinocytes from Fine Particulate Matter (PM2.5)-Induced Oxidative Stress and Apoptosis by Inhibiting the Endoplasmic Reticulum Stress Response - Ilandarage Menu Neelaka Molagoda; Mirissa Hewage Dumindu Kavinda; Yung Hyun Choi; Hyesook Lee; Chang-Hee Kang; Mi-Hwa Lee; Chang-Min Lee; Gi-Young Kim (MDPI AG, 2021)
Fine particulate matter (PM2.5) originates from the combustion of coal and is found in the exhaust of fumes of diesel vehicles. PM2.5 readily penetrates the skin via the aryl hydrocarbon receptor, causing skin senescence, inflammatory skin diseases, DNA damage, and carcinogenesis. In this study, we investigated whether fisetin, a bioactive flavonoid, prevents PM2.5-induced apoptosis in HaCaT human keratinocytes. The results demonstrated that fisetin significantly downregulated PM2.5-induced apoptosis at concentrations below 10 μM. Fisetin strongly inhibited the production of reactive oxygen species (ROS) and the expression of pro-apoptotic proteins. The PM2.5-induced apoptosis was associated with the induction of the endoplasmic reticulum (ER) stress response, mediated via the protein kinase R-like ER kinase (PERK)-eukaryotic initiation factor 2α (eIF2α)-activating transcription factor 4 (ATF4)-CCAAT-enhancer-binding protein (C/EBP) homologous protein (CHOP) axis. Additionally, the cytosolic Ca2+ levels were markedly increased following exposure to PM2.5. However, fisetin inhibited the expression of ER stress-related proteins, including 78 kDa glucose-regulated protein (GRP78), phospho-eIF2α, ATF4, and CHOP, and reduced the cytosolic Ca2+ levels. These data suggest that fisetin inhibits PM2.5-induced apoptosis by inhibiting the ER stress response and production of ROS.